The Role of Hemoglobin Oxidation Products in Triggering Inflammatory Response Upon Intraventricular Hemorrhage in Premature Infants - Erdei, Judit; Tóth, Andrea; Nagy, Andrea; Nyakundi, Benard Bogonko; Fejes, Zsolt; Nagy Jr., Béla; Novák, László; Bognár, László; Balogh, Enikö; Paragh, György; Kappelmayer, János; Bácsi, Attila; et al. (Frontiers in Immunology, 2020)
Intraventricular hemorrhage (IVH) is a frequent complication of prematurity that is associated with high neonatal mortality and morbidity. IVH is accompanied by red blood cell (RBC) lysis, hemoglobin (Hb) oxidation, and sterile inflammation. Here we investigated whether extracellular Hb, metHb, ferrylHb and heme contribute to the inflammatory response after IVH. We collected cerebrospinal fluid (CSF) (n=20) from premature infants with grade III IVH at different time points after the onset of IVH. Levels of Hb, metHb, total heme and free heme were the highest in CSF samples obtained between days 0-20 after the onset of IVH and were mostly non-detectable in CSF collected between days 41-60 of post-IVH. Besides Hb monomers, we detected crosslinked Hb dimers and tetramers in post-IVH CSF samples obtained in days 0-20 and 21-40, but only Hb tetramers were present in CSF samples obtained after 41-60 days. VCAM-1 and IL-8 levels were higher in CSF samples obtained between days 0-20 than in CSF collected between days 41-60 of post-IVH. Concentrations of VCAM-1, ICAM-1 and IL-8 strongly correlated with total heme levels in CSF. Applying the identified heme sources on human brain microvascular endothelial cells revealed that Hb oxidation products and free heme contribute to the inflammatory response. We concluded that RBC lysis, Hb oxidation and heme release are important components of the inflammatory response in IVH. Pharmacological interventions targeting cell-free Hb, Hb oxidation products and free heme could have potential to limit the neuro-inflammatory response following IVH.